A Stability-Indicating HPLC-DAD Method for Determination of Stiripentol: Development, Validation, Kinetics, Structure Elucidation and Application to Commercial Dosage Form. (13th October 2014) - Darwish, Hany W.; Abdelhameed, Ali S.; Attia, Mohamed I.; Bakheit, Ahmed H.; Khalil, Nasr Y.; Al-Majed, Abdulrahman A.
Abstract : A rapid, simple, sensitive, and accurate isocratic reversed-phase stability-indicating high performance liquid chromatography method has been developed and validated for the determination of stiripentol and its degradation product in its bulk form and pharmaceutical dosage form. Chromatographic separation was achieved on a Symmetry C18 column and quantification was achieved using photodiode array detector (DAD). The method was validated in accordance with the ICH requirements showing specificity, linearity (r 2 = 0.9996, range of 1–25 μ g/mL), precision (relative standard deviation lower than 2%), accuracy (mean recovery 100.08 ± 1.73 ), limits of detection and quantitation (LOD = 0.024 and LOQ = 0.081 μ g/mL), and robustness. Stiripentol was subjected to various stress conditions and it has shown marked stability under alkaline hydrolytic stress conditions, thermal, oxidative, and photolytic conditions. Stiripentol degraded only under acidic conditions, forming a single degradation product which was well resolved from the pure drug with significantly different retention time values. This degradation product was characterized by 1 H-NMR and 13 C-NMR spectroscopy as well as ion trap mass spectrometry. The results demonstrated that the method would have a great value when applied in quality control and stability studies for stiripentol.